Dealing With the Media. - Selinger, C. (IEEE spectrum)
The author suggest a few guidelines on how to deal with reporters. At some point in your carrer you'll need to have this soft skill - to explain, defend, or promote a project to your boss, a reporter, or your company's communications manager.